Synthesis and antitubercular activity of new thiazolidinones with pyrazinyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Khillare, Lalit D.; Arkile, Manisha A.; Sarkar, Dhiman; Mane, Ramrao A. (Journal of Heterocyclic Chemistry, 2017)
Emergence of multidrug resistant and extensively drug resistant tuberculosis has prompted to develop new molecular entities to treat the disease. A series of new 4-thiazolidinones with pyrazinyl and thiazolyl scaffolds has been synthesized, and their antitubercular activity is reported. The title 4-thiazolidinones, N-(pyrazinyl substituted thiazoloylamino)-2-aryl-4-thiazolidinones () have been first time prepared using pyrazinamide as a starting material via five successive steps. The purity and the structures of the intermediates (carboethoxythiazole, acid hydrazide, and azomethines) and title thiazolidinones () have been confirmed by TLC and spectral analyses, respectively. An antitubercular screening of the new 4-thiazolidinones has been performed on bacterial strains, Mycobacterium tuberculosis H37Ra and Mycobacterium BCG using the solutions of different concentrations of the compounds () and the screening results are presented. Compound has displayed notable antitubercular activity.